In Vivo Vascularization of Cell-Supplemented Spider Silk-Based Hydrogels in the Arteriovenous Loop Model - Osterloh, Justus; Heltmann-Meyer, Stefanie; Trossmann, Vanessa T.; Cai, Aijia; Kulicke, Yvonne; Terörde, Klara; Sörgel, Celena; Lang, Isabell; Wajant, Harald; Scheibel, Thomas; Fey, Tobias; Steiner, Dominik; et al. (Biomimetics, 2025)
The goal of reconstructive surgery in treating tissue defects is to achieve a stable reconstructive outcome while minimizing donor site morbidity. As a result, tissue engineering has emerged as a key focus in the pursuit of this goal. One approach is to create a tissue container that can be preconditioned and later transplanted into the defect area. The characteristics of the matrices used in the tissue container are critical to this approach’s success. Matrices generated with recombinant, functionalized spider silk (eADF4(C16)-RGD) have been reported to be biocompatible and easy to vascularize. However, the effect of exogenously added proangiogenic cells, such as endothelial cells (T17b), on the vascularization process of matrices generated with this hydrogel in vivo has not been described yet. In this study, we implanted arteriovenous (AV) loop containers filled with a spider silk hydrogel consisting of an eADF4(C16)-RGD matrix and encapsulated, differentiated endothelial T17b cells producing the reporter protein TNFR2-Fc-Flag-GpL. The histological and µCT analyses revealed spontaneous angiogenesis and fibrovascular tissue formation in the container at 2 and 4 weeks post-implantation. The reporter protein was detected after 4 weeks. No severe immune response was observed. Altogether, this study demonstrates that cell-supplemented recombinant spider silk is a highly promising hydrogel to produce matrices for tissue engineering applications.
CRIS-Team Scopus Importer:2025-03-14
Keywords: recombinant spider silk; reconstructive surgery; tissue engineering; vascularization

Recombinant Human Growth Hormone Activates Neuroprotective Growth Factors in Hypoxic Brain Injury in Neonatal Mice - Jung, Susan; Terörde, Klara; Dörr, Helmuth-Günther; Trollmann, Regina (Endocrinology, 2021)
Perinatal hypoxia severely disrupts cerebral metabolic and maturational programs beyond apoptotic cell death. Antiapoptotic treatments such as erythropoietin are suggested to improve outcomes in hypoxic brain injury; however, the results are controversial. We analyzed the neuroprotective effects of recombinant human growth hormone (rhGH) on regenerative mechanisms in the hypoxic developing mouse brain in comparison to controls. Using an established model of neonatal acute hypoxia (8% O2, 6 hours), P7 mice were treated intraperitoneally with rhGH (4000 µg/kg) 0, 12, and 24 hours after hypoxic exposure. After a regeneration period of 48 hours, expression of hypoxia-inducible neurotrophic factors (erythropoietin [EPO], vascular endothelial growth factor A [VEGF-A], insulin-like growth factors 1 and 2 [IGF-1/-2], IGF binding proteins) and proinflammatory markers was analyzed. In vitro experiments were performed using primary mouse cortical neurons (E14, DIV6). rhGH increased neuronal gene expression of EPO, IGF-1, and VEGF (P < .05) in vitro and diminished apoptosis of hypoxic neurons in a dose-dependent manner. In the developing brain, rhGH treatment led to a notable reduction of apoptosis in the subventricular zone and hippocampus (P < .05), abolished hypoxia-induced downregulation of IGF-1/IGF-2 expression (P < .05), and led to a significant accumulation of endogenous EPO protein and anti-inflammatory effects through modulation of interleukin-1β and tumor necrosis factor α signaling as well as upregulation of cerebral phosphorylated extracellularly regulated kinase 1/2 levels (ERK1/2). Indicating stabilizing effects on the blood-brain barrier (BBB), rhGH significantly modified cerebrovascular occludin expression. Thus, we conclude that rhGH mediates neuroprotective effects by the activation of endogenous neurotrophic growth factors and BBB stabilization. In addition, the modification of ERK1/2 pathways is involved in neuroprotective actions of rhGH. The present study adds further evidence that pharmacologic activation of neurotrophic growth factors may be a promising target for neonatal neuroprotection.
CRIS-Team Scopus Importer:2021-03-05
Keywords: apoptosis; BBB; IGF binding proteins; IGF-1; IGF-2; interleukin-1β; neuroprotection; occludin; pERK 1/2; TNF-α; VEGF